Theory of optimising radiation protection among diagnostic radiographers depicted as a model - Shantel Lewis; Charlene Downing; Christopher M. Hayre (AOSIS, 2024)
Background: When radiation protection practices are suboptimal, it becomes necessary to take additional steps to optimise practices. Aim: Therefore, this study aimed to develop a model to facilitate radiation protection among diagnostic radiographers. Setting: The study was conducted in South Africa. Methods: A theory-generating design consisting of three steps was used to develop the model: (1) the central concept was identified, defined and classified; (2) relationship statements were created and (3) the model was developed, described and evaluated. Results: The model was premised on the central concept of facilitating a transformative radiation protection environment and occurs in four phases: (1) relationship, (2) working, (3) termination and (4) independent phases. The radiography manager and radiographer enter the relationship phase of the model because of discord regarding radiation protection in their department and work together to optimise radiation protection. The model's purpose, assumptions, context, structure and process are described. Conclusion: A model to facilitate radiation protection among radiographers was conceptualised to optimise radiation protection. The model details the steps the radiography manager and radiographer take to co-create optimal radiation protection practices. Radiation protection compliance among radiographers is paramount to ethical radiography practice, and the model provides a guide to optimise radiation protection. Contribution: In any radiography department where radiation protection may be lacking, the model provides a road map of possibilities for change. Ultimately, radiation protection compliance improves patient care and outcomes.